2014
DOI: 10.1097/tp.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Donor-Specific Antibodies in Acute Cardiac Allograft Dysfunction in the Absence of Cellular Rejection

Abstract: Background Acute allograft dysfunction (AAD) is an important cause of morbidity among heart transplant recipients. The role of donor specific antibodies (DSA) in AAD, with the increasing use of Single Antigen Bead (SAB) assays that have improved the ability to detect DSA, remains unclear. Methods We retrospectively reviewed 329 heart transplant recipients followed at our institution. AAD was defined as an acute decline in left ventricular ejection fraction to <50% and a decrement of ≥10% compared to baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…3,23,24 More recent studies have addressed the use of MFI levels for HLA antibodies and found some utility in using these measurements in acute allograft vasculopathy. 25 There is increasing evidence, however, that Class II DSA are more strongly associated with long-term chronic rejection, particularly in the form of CAV. 6,26 Interestingly, Smith et al 5 showed no association between HLA antibodies (DSA or non-DSA) and the development of CAV.…”
Section: Discussionmentioning
confidence: 99%
“…3,23,24 More recent studies have addressed the use of MFI levels for HLA antibodies and found some utility in using these measurements in acute allograft vasculopathy. 25 There is increasing evidence, however, that Class II DSA are more strongly associated with long-term chronic rejection, particularly in the form of CAV. 6,26 Interestingly, Smith et al 5 showed no association between HLA antibodies (DSA or non-DSA) and the development of CAV.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the prognostic importance of DSAs is influencing initial immunosuppressive protocols according to patients’ pre-transplantation DSA status. Recipients with pre-transplantation DSA are far more likely to experience antibody-mediated or cellular rejection and graft failure despite desensitization measures, which is hard to apply to heart transplantation as the pool of organs is smaller, heart grafts are less well-matched than other organs, transplantation is more urgent, and graft storage times are shorter, and it is often not possible to await the results of cross-match testing [ 16 , 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute cardiac allograft dysfunction without the presence of donor-specific anti-HLA antibodies can occur in up to 40% of cases. Most of these heart transplant recipients are responsive to augmented immunosuppression suggestive of immune-mediated non-HLA-mediated graft dysfunction [6].…”
Section: Introduction and Scope Of The Problemmentioning
confidence: 99%